Proteína bruta na dieta e características reprodutivas de codornas japonesas (Coturnix coturnix japonica) machos e fêmeas - Retes, Pâmela Lacombe (2018)
The aim was to evaluate the effects of different dietary crude protein (CP) levels in male and female Japanese quails. Two experiments were carried out: one to evaluate CP variation according to growth and production diets (experiment 1), and another to evaluate CP variation only in the growth phase (experiment 2). Initially, 300 one-day-old males and 640 one-day-old females were housed in 30 cages containing 10 males each (6 cages per treatment) and 10 cages with 36 females each (2 cages per treatment). In addition, 8 extra cages containing 35 birds each were used to house 280 additional females for the fertility test of the males. Five levels of dietary CP were used (18, 20, 22, 24, and 26%) up to 35 days of age. From that age, the birds were redistributed in 70 cages containing nine females and three males each. Birds from forty cages (eight per treatment) continued to be fed diets with different CP levels, but reduced by four percentage units (14, 16, 18, 20, and 22%) relative to the previous phase. The other 30 cages (6 for each treatment) received only feed with the CP levels recommended for this phase (18%). Throughout the experiment, a completely randomized design was used. Every 3 days until 60 days of age, 12 birds from each plot were individually weighed to determine the growth curve. The males from experiment 1 demonstrated a linear increase (P<0.01) in growth rate with increasing CP. A highest weight at maturity (P<0.05) was obtained with 18% PB. There was no effect (P<0.05) of CP on the histological characteristics of the testes or the physiological characteristics of the semen, or on fertility. In females, 24 and 26% CP reduced (P<0.01) the growth rate and increased (P<0.05) the age of maximum weight gain. The level of 24% CP resulted in higher (P<0.01) weight at maturity, whereas 26% showed lower (P<0.01) age at the first egg and higher egg mass compared to other CP levels. At 47 days, the highest posture intensity (P<0.05) was obtained with 24 and 26% CP. The growth rate of the males from experiment 2 and the histological development of the testes increased linearly (P<0.01) with increase of dietary CP. However, there was no effect (P>0.05) on semen characteristics or fertility. In females at 36 days, CP stimulated (P<0.05) the anatomical development of the ovaries, however, this effect was not observed (P<0.05) at later ages. At 48 days, a linear increase in posture intensity was observed (P<0.01) with increasing dietary CP. A linear increase (P<0.05) in egg weight was observed until the end of the experiment. There was no effect (P>0.05) on the internal characteristics of the egg. It is concluded that dietary CP levels influence the body development of males and females but only affect the reproductive quality of females. For a higher production up to the peak of posture and a higher egg weight after this phase, it is recommended to use 26% CP in growth diets and 22% in production diets.